New Keynesian Phillips Curves: a reassessment using euro-area data - Peter McAdam; Alpo Willman (European Central Bank (ECB), 2003)
Using euro-area data, we re-examine the empirical success of New Keynesian Phillips Curves (NKPCs). The nature of our re-evaluation relies on the actual empirical underpinnings of such estimates: we find existing estimates un-robust and – given that key parameters are generally calibrated rather than estimated – potentially at odds with the data. We re-estimate with a wellspecified optimizing supply-side (which attempts to treat non-stationarity in factor income shares and mark-ups) and this allows us to derive estimates of technology parameters and marginal costs. Our resulting estimates of the euro-area NKPCs are robust, provide reasonable estimates for fixed-price durations and discount rates and embody plausible dynamic properties. Our method for identifying and estimating New Keynesian Phillips curves has general applicability to a wide set of countries and might also be used in identifying sectoral NKPCs.
Keywords: E31; 330; Euro-Area; Inflation Dynamics; Phillips Curves; Supply-Side